Hankel determinant for functions starlike and convex with respect to symmetric points - Aini Janteng,; Suzeini Abdul Halim,; Maslina Darus, (Penerbit ukm, 2006)
Sakaguchi (1959) introduced the class of functions S*s , starlike with respect to symmetric points. In 1977, Das and Singh introduced similar class of functions Cs , convex with respect to symmetric points. Here, upper bound for the functional |a2a4-a23| is attained for functions f(z)=z+ ∑ anzn belonging to S*s and Cs . The result obtained is sharp